Characterization of age-dependent variability in the flank scales of two scorpaeniformes fishes by applying light and scanning electron microscopy imaging - Motamedi, Mina; Teimori, Azad; Amiri, Vahid; Hesni, Majid Askari (Micron (Oxford, England : 1993), 2020)
•The posterior margin of ctenoid scales in the examined fishes is formed by two rows of cteni, while the three complete rows were not observed.•The number of cteni in the studied scales was increased during fish development, while their general morphology was not changed properly.•The number of cteni in the scales of the small and large fishes in G. suppositus was obviously lower than Platycephalus indicus.•The scale ornamentations were subject of the modification during fish development. The morphology of scales from four flank regions in two species of Scorpaeniforme fishes of the family Platycephalidae was studied by applying light and scanning electron microscopy, and the age-dependent variability of scale structures was discussed. The scales of four flank regions from three size classes in both species were ctenoid. The posterior margin of all the ctenoid scales was formed by two rows of cteni, while the three complete rows of cteni were not observed in the examined scales. The cteni of both rows were similar in morphology. Some scale characteristics showed alteration during the fish growth, including the shape of the anterior region of scale in Platycephalus indicus, the presence of lepidonts in Grammoplites suppositus, and the general shape of scale as well as the indices SCL.SCW and JSW.SL in both species. Also, the number of cteni in posterior margin of scales was increased during fish development, while their general morphology did not change significantly. The number of cteni in the scales of small and large fishes in G. suppositus was found to be obviously lower than P. indicus. By considering the function of lepidonts in improving the hydrodynamic efficiency of swimming, it can be assumed that G. suppositus is not probably very active in swimming as P. indicus. As a conclusion, modification in the ornamentations of the posterior region are subject to alteration during the growth of the fish. Besides its developmental changes, some scale characters in the adult forms have taxonomic significance, including the square-shaped scales in P. indicus vs. the oval-shaped scale in G. suppositus; a total of 26–31 radii in the anterior field in P. indicus vs. 11–12 radii in G. suppositus; the presence of many (54–58) cteni in the posterior part in P. indicus vs. a moderate (19–23) cteni in G. suppositus. These characters could be used as additional morphological data to be used for studying systematics and even phylogeny of the flathead fishes.